Next-Generation Simulation—Integrating Extended Reality Technology Into Medical Education - Herur-Raman, Aalap; Almeida, Neil D.; Greenleaf, Walter; Williams, Dorian; Karshenas, Allie; Sherman, Jonathan H. (Frontiers in Virtual Reality, 2021)
In recent years, the advancement of eXtended Reality (XR) technologies including Virtual and Augmented reality (VR and AR respectively) has created new human-computer interfaces that come increasingly closer to replicating natural human movements, interactions, and experiences. In medicine, there is a need for tools that accelerate learning and enhance the realism of training as medical procedures and responsibilities become increasingly complex and time constraints are placed on trainee work. XR and other novel simulation technologies are now being adapted for medical education and are enabling further interactivity, immersion, and safety in medical training. In this review, we investigate efforts to adopt XR into medical education curriculums and simulation labs to help trainees enhance their understanding of anatomy, practice empathetic communication, rehearse clinical procedures, and refine surgical skills. Furthermore, we discuss the current state of the field of XR technology and highlight the advantages of using virtual immersive teaching tools considering the COVID-19 pandemic. Finally, we lay out a vision for the next generation of medical simulation labs using XR devices summarizing the best practices from our and others’ experiences.